Do Social Enterprises Discriminate Less Than For-Profit Organizations? The Influence of Sector and Diversity Policies on Managers' Prejudice Toward Immigrants. (August 2018) - Brolis, Olivier; Courtois, Marie; Herman, Ginette; Nyssens, Marthe
During the past 15 years, discrimination in work settings has become an increasing problem. The social enterprise (SE) and nonprofit literature suggests that these organizations discriminate against workers less frequently than for-profit organizations (FPOs). In the field of social psychology, it has been assumed that a multicultural approach to managing diversity would improve relationships among workers with different ethnic or cultural origins. This study examines the relationships between managers' attitudes toward immigrants and the organization's characteristics, namely, organizational multiculturalism, the organization's sector (FPO or SE), and organization's mission (i.e., work integration, home care services, and profit making). The survey was conducted among managers of organizations involved in the Belgian service voucher system. The results indicate that managers in work integration SEs are less prejudiced than managers in FPOs and home care services organizations, and that the more the workforce diversity is managed through a multicultural approach, the less prejudiced managers are.